Systemic Immune-inflammation Index in Evaluation of Inflammation in Rheumatoid Arthritis Patients - Amela DERVISEVIC; Almir FAJKIC; Elmedina JAHIC; Lejla DERVISEVIC; Zurifa AJANOVIC; Enisa ADEMOVIC; Asija ZACIRAGIC (Medeniyet Medical Journal)
Objective: To evaluate the systemic immune-inflammation (SII) index in patients with rheumatoid arthritis (RA) stratified by systemic inflammatory status. Methods: Seropositive patients with RA (n=58) were divided into two groups based on serum hs-C-reactive protein (hs-CRP) levels: RA patients with hs-CRP levels of at or 3 mg/L or above (high systemic inflammatory status; n=38) and RA patients with hs-CRP levels of less than 3 mg/L (low systemic inflammatory status; n=20). The control group comprised 31 healthy individuals. Blood samples were tested for the next parameters: leukocytes, neutrophilic granulocytes, lymphocytes, thrombocytes [platelet (PLT)], high-sensitivity hs-CRP, sed rate [erythrocyte sedimentation rate (ESR)], neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), and monocyte-to-lymphocyte ratio (MLR). The SII index was derived as Neu x PLT/Lym. Results: In patients with RA, the SII index was elevated compared with that of healthy individuals and positively correlated with hs-CRP, erythrocyte sedimentation rate, NLR, MLR, PLR, tender joint count, and swollen-to-tender joint count ratio. Patients with RA who had hs-CRP levels of 3 mg/L above exhibited a statistically significant increase in the SII compared with those with hs-CRP levels below 3 mg/L. Additionally, within the cohort of RA patients with hs-CRP levels at or above 3 mg/L, a positive correlation was found between the SII index and both NLR and PLR. The SII index was positively correlated with NLR, MLR, and PLR in RA patients with hs-CRP levels below 3 mg/L. The cut-off point of the SII index for distinguishing between RA cases with hs-CRP levels 3 mg/L and those with hs-CRP levels 3 mg/L or higher was ≥323.4, with a sensitivity of 77.6% and a specificity of 54.8%. Conclusions: The serum SII index can be a potentially useful marker for evaluating the inflammatory process and clinical progression of RA.